Peran Sains dan Teknologi Dalam Meningkatkan Kualitas Hidup Masyarakat - Fitriyadi, Adi; Syafe’i, Abdullah; Gunawan, Indra; Ramadhan, Ismil Nur; Gunawan, Izwan; Yulianti, Jihan; Nuralim, Ma’rij; Ropik, Muhammad; Riyantini, Ranti; Febrina, Syarah Intan; Ramadhan, Valiant Bintang; Johari, Ganjar Jojon (Institut Teknologi Garut, 2022)
Currently we are being hit by the COVID-19 pandemic which of course has an impact on all sectors, especially the world of education, where inevitably teaching and learning activities throughout Indonesia must be carried out online. In addition, there are restrictions on community activities that have been implemented on a large scale so that the scope of community movement is limited. The virtual world is one way that can be used to continue to be creative and add insight in order to become a much better generation. Therefore, this is where technology plays a role. Many of the nation's next generations are starting to be active in carrying out productive activities from home through virtual communities. One form of activity is a webinar. Webinars are seminars that are held online where the themes raised are hot issues or topics in society.